1991
DOI: 10.1002/bjs.1800780111
|View full text |Cite
|
Sign up to set email alerts
|

Study of belching ability in antireflux surgery patients and normal volunteers

Abstract: The ability to belch was evaluated by a novel test, after gaseous stomach distension to standard volume, in 16 patients after antireflux surgery and nine healthy volunteers. A structured assessment of dyspeptic symptoms was also carried out in both groups. Repeat studies in volunteers showed acceptable reproducibility for the new test of belching capacity (within-subject coefficient of variance 4.5 per cent). After antireflux surgery, patients had lower volume individual belches (median(range) 27.5(0-104) ml i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This slightly increased after two years to 53%. In some patients fundoplication procedures impair the ability to belch and thereby to relieve bloating [41]. The inability to belch occurred in about 25% of patients in the Nissen group and in 13% in the Toupet group.…”
Section: Discussionmentioning
confidence: 95%
“…This slightly increased after two years to 53%. In some patients fundoplication procedures impair the ability to belch and thereby to relieve bloating [41]. The inability to belch occurred in about 25% of patients in the Nissen group and in 13% in the Toupet group.…”
Section: Discussionmentioning
confidence: 95%
“…However, recent meta-analyses have demonstrated that a substantial number of patients report gas-related symptoms and persistent refractory reflux symptoms after this procedure 4 9 10. Inability to belch has been postulated to cause the gas-related symptoms, but the impact of fundoplication on belching has only been evaluated indirectly 17 20 23–25. Weakly acidic reflux has been alleged to be the main cause of persistent reflux complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that evaluated belching after fundoplication were methodologically limited by the fact that belches were recorded indirectly, using an experimental method to quantify belched volumes20 or manometric common cavities 17 23–25. Four of these studies20 23–25 evaluated post-fundoplication patients and only one study17 compared belching before and after surgery. As a result, the current report is the first study to directly evaluate the impact of fundoplication on belching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly assumed that an inability to vent air from the stomach by gastric belching causes gas-related symptoms. [9][10][11][12][13][14][15] A previous study indeed demonstrated that patients with an objective reduction of gastric belches (GBs) after fundoplication, have higher symptom scores for inability to belch and gas bloating, compared with patients who not have an objective reduction of GBs. 16 Our group has recently demonstrated that after 360 degrees LPF the number of GBs is significantly reduced.…”
mentioning
confidence: 99%